THE RELATIONSHIP BETWEEN CURRICULUM AND EDUCATIONAL POLICY IN IMPROVING HUMAN RESOURCE QUALITY: A LITERATURE REVIEW - Mudzakir Mudzakir; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine in depth the relationship between curriculum and education policy in efforts to improve the quality of human resources (HR) in Indonesia. Using a literature review approach, this study analyses theories, concepts, and previous research findings related to curriculum development, education policy formulation, and their implications for HR quality. The findings indicate that synergy between adaptive curricula and responsive education policies is a key factor in shaping competent, innovative, and competitive human resources in the global era. Strategic policies that emphasise the relevance of curricula, the professionalism of educators, and equitable access to education can accelerate the sustainable transformation of human resource quality. This study recommends the need for evaluation and cross-sectoral collaboration in curriculum and policy development to produce high-quality human resources that align with societal needs and national development demands.